Quantum Guarded-Command Language (qGCL) for Maximum Value - Putri, Aisya; Titaley, Jullia; Pinontoan, Benny (Universitas Sam Ratulangi, 2017)
On a classical computer or a binary computer, calculations are done simultaneously so as to produce the equations and algorithms. The result of this research shows that to determined maximum value specified in the algorithm using quantum Guarded-Command Language (qGCl) in quantum computer. Initially determine of maximum value was construct in Djikstra’s Guarded-Command Language (GCL) which is then implemented on Zuliani’s probability Guarded-Command Language (pGCL) furthermore applying to quantum Guarded-Command Language (qGCL) for last result. Of concern here is the speed in resolving a problem or calculate problem. Due to the Quantum Computer has a Quantum Bit (qubit) and a phenomenon commonly called superposition. Keywords: GCL, pGCL, qGCL, quantum computer.